Performance evaluation of a multi-stage solar distiller associated with Fresnel lens in Malaysian weather - Yeang, Jonathan Yong Kai; Bahar, Rubina; Koo, Chai Hoon; Lee, Sze Shin (Frontiers in Energy Research, 2023)
Water scarcity is widely known as one of the huge current issues. As of now, many solar distillers are using the same concept of evaporation and condensation of saline water to produce distillate. The main problem of such solar distiller is its low productivity, as the latent heat produced is loss to surrounding. A multi-stage solar distiller is able to solve the issue of productivity by utilizing the latent heat released. This design consists of multiple solar distillers stacked on top of one another, producing distillate in each stage while having the same amount of energy intake. Malaysia falls within the tropical belt where solar radiation appears to be diffused, resulting in low-quality heat energy that can be absorbed. To solve this problem, concentrated solar power (CSP) technology has been introduced. However, CSP technology can be very expensive, thus using Fresnel lens as a direct refraction device will be a cheaper option. In this study, a four-stages solar distiller system integrated with Fresnel lenses is introduced. It was found that the productivity and efficiency of the multi-stage system is higher, with a productivity of 0.164 g/kJ and efficiency of 39.5% comparing to the single stage solar distiller with a productivity of 0.104 g/kJ with an efficiency of 23.5%.